2009
DOI: 10.1038/aps.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

A sesquiterpene quinone, dysidine, from the sponge Dysidea villosa, activates the insulin pathway through inhibition of PTPases

Abstract: Aim:The sesquiterpene hydroquinones/quinones belong to one class of marine sponge metabolites, and they have received considerable attention due to their varied biological activities, including anti-tumor, anti-HIV, and anti-inflammatory action. In order to probe the potential anti-diabetic effect of the sesquiterpene hydroquinones/quinones, the effect of dysidine on the insulin pathway was studied. Methods: The promotion of glucose uptake by dysidine was studied in differentiated 3T3-L1 cells. The increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 46 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…Inhibitory effects on the enzyme PTP1B have been reported for a polybromodiphenyl ether from the Indonesian marine sponge Lamellodysidea herbacea [75] and for the terpene Dysidine, from the sponge Dysidea sp. [23,76], that has recently entered pre-clinical trials for the treatment of type-2 diabetes [23]. Dysidine was found for the first time in a sponge at Lahdu (Santo) in Vanuatu in June 1996, identified as sponge Dysidea sp.…”
Section: Marine Macroorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
“…Inhibitory effects on the enzyme PTP1B have been reported for a polybromodiphenyl ether from the Indonesian marine sponge Lamellodysidea herbacea [75] and for the terpene Dysidine, from the sponge Dysidea sp. [23,76], that has recently entered pre-clinical trials for the treatment of type-2 diabetes [23]. Dysidine was found for the first time in a sponge at Lahdu (Santo) in Vanuatu in June 1996, identified as sponge Dysidea sp.…”
Section: Marine Macroorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
“…The chemical study on another Dysidea sp led to the discovery of a new sesquiterpene quinone (42), along with a known related analog dysidine (43) [31] ( Figure 7). A bioassay showed that dysidine (43) µmol/L, respectively [32] . Three unprecedented diastereoisomeric dimers, cis-dimers A (44) and B (45) and trans-dimer C (46), representing bisbisabolene skeletons, and their potential precursor dehydrotheonelline (47) have been isolated from the South China Sea sponges Axinyssa variabilis and Lipastrotethya ana [33] ( Figure 7).…”
Section: Chemical Studies On Chinese Invertebratesmentioning
confidence: 99%
“…145 Subsequent studies showed that it effectively activated the insulin signaling pathway and greatly promoted glucose uptake in 3T3-L1 cells. 146 From the roots of Suussurea lappa, Hu obtained one new lignan glycoside along with 20 known compounds, which were tested against PTP1B. 147 Rhein-8-O-b-Dglucopyrariosidc (113) showed the best activity with an IC 50 of 11.5 mM.…”
Section: Natural Products and Derivativesmentioning
confidence: 99%